Discretionary stock halt and analyst forecast - Xuehang Yu; Junxiong Fang (China Journal of Accounting Studies (CJAS), 2021)
The increasing number of discretionary stock halts, has attracted the attention of regulatory authorities and scholars. They have also become a significant obstacle to the internationalization of China's capital market. This article systematically examines the impact of discretionary halts on the information environment from the perspective of analysts. The study finds that discretionary halts lead to a decrease in the number of analysts following, a decline in analysts' forecast accuracy, and an increase in analysts' forecast dispersion. Further research finds that reducing the amount and the decline of the quality of information disclosure are two crucial channels for discretionary stock halts deteriorating the information environment. Cross-sectional tests show that the impact of discretionary stock halts is more pronounced in samples with lower investor protection and higher agency costs. Above results indicate that the discretionary halt deteriorates the company's information environment, which provides important policy implications for China's capital market reform.
Keywords: 650; Discretionary stock halt; information environment; analyst forecast